Displacement as a Diasporic Experience in V.S. Naipaul’s A House for Mr Biswas - Rai, Ram Prasad (Crossing the Border: International Journal of Interdisciplinary Studies, 2017)
The term ‘displacement’ has a strong connection with diaspora literature that studies the experiences of pain and pleasure of the people in the diaspora. People in the diaspora do not have comfortable life. Since they are away from their homeland, it is not easy for them to get integrated into the new main stream society. Because of several variations such as language, culture, custom, religion, belief etc., they are to face difficulties in the host-land. They come across the feeling of displacement through alienation, homelessness, identity crisis etc. that are interconnected in the diaspora. Being a generation of indentured labor immigrant family, V. S. Naipaul himself has gone through such paining experiences that are indirectly expressed through the life experiences of the characters in his writing. While reading about Naipaul’s life story and of Mr. Biswas in the novel A House for Mr. Biswas, it can be understood that they sound similar strongly. In the novel, Naipaul shows how Mr. Biswas more importantly along with other people as the generation of indentured labour immigrant parents in Trinidad suffer from homelessness, displacement, alienation etc. This paper mainly focuses on the experiences of displacement along with homelessness, alienation etc. faced by Mr. Biswas and other characters as they are from Indian diasporic community. Crossing the Border: International Journal of Interdisciplinary Studies 5(2) 2017: 25-30